The effect of hemofilter, preoperative and intraoperative methylprednisolone on complications after open heart surgery - . Supomo; Teguh Aryandono; Marsetyawan Soesatyo; Paulus Sudiharto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2017)
Complications after open heart surgery may threaten patient’s survival rate. Theintraoperative methylprednisolone administration alone shows controversial resultson open heart surgery complications. Similarly, the intraoperative and preoperativemethylprednisolone administration as well as the use of hemofilter in open heart surgeryis still controversial. This study aimed to evaluate the effect of hemofilter, preoperativeand intraoperative methylprednisolone administration on complications following openheart surgery. This was a Prospective Randomized Open-Blinded Evaluation (PROBE)experimental study. Ninety-five patients who had open heart surgery in Dr. SardjitoGeneral Hospital, Yogyakarta, and Integrated Cardiac Care of Dr. Cipto MangunkusumoGeneral Hospital, Jakarta within the period of December 2011 to May 2012 wereinvolved in this study. The patients were divided into two groups i.e. group A, 48 patientsreceived methylprednisolone 15mg/kg intraoperatively, methylprednisolone 5mg/kgpreoperatively, and hemofilter, while group B, 47 patients received methylprednisolone15mg/kg intraoperatively alone. From the total 95 patients, we found 26 (27.4%)patients experienced complications i.e. 19 in group B (40.4%) and 7 in group A(14.6%). The differences of the complications were statistically significant (p<0.05;OR=3.97; 95%CI=1.476-10.71). Complications risk decreased by 63.9% in the groupA compared to the group B with the hazard ratio of 3.2. In conclusion, the application ofhemofilter, preoperative and intraoperative methylprednisolone might decrease the risk ofcomplications after open heart surgery.